(untitled) - Louis A. Goldstein (New York, 1981)
1. Shoulder 2. Upper arm 3. Elbow 4. Forearm 5. Wrist 6. Hand 7. Neck and cervical spine 8. Thoracolumbar spine 9. Pelvis 10. Hip 11. Thigh 12. Knee 13. Lower leg 14. Ankle 15. Foot 16. Miscellaneous operative procedures
Keywords: orthopedic surgery - atlases